Avaliação de oponentes en confrontos de tilápia-do-Nilo: interação entre sinais químicos e visuais - Pinho Neto, Cândido Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
During the establishment of contests between individuals of the same species, the factors usually described as mediators for access to information of the opponent are visual signals, such as size, coloration patterns and ritualized behaviors. Despite the importance of visual signals for communication in fish, other signals are important in this complex system. Considering the aquatic environment and the facilitated dispersion of chemicals released by individuals, it is presumed that chemical signaling may be involved in the assessment of opponents and the decision making before and / or during a contest. Thus, this study tested the effects of chemical signals and their integration with visual signals (size of the opponent) in aggressive behavior in contests between individuals of the species Oreochromis nilocticus (Nile Tilapia). To test this hypothesis, pairs were matched in a condition in which individuals could see each other, but there was no mechanical or chemical contact between them. For the contest, the focal fish of the pair was stimulated with chemical and visual signals from conspecifics, comprising the following conditions: chemical stimuli 1) conditioned water by a smaller conspecific, 2) same-sized 3) larger or 4) water; and visual stimuli 1) smaller opponent, 2) same-sized, or 3) larger. In the groups that viewed a smaller opponent, the different treatments did not change the aggressive behavior of focal fish. When viewing an opponent of the same size, individuals receiving chemical signals from size-matched and larger conspecifics showed a reduction in the expression of attacks when compared to the control group. And, viewing a larger opponent, the display time reduced regardless of the chemical stimulus and the number of attacks increased in the group receiving chemical signals from larger conspecifics when compared to control and smaller. The results show that the Nile Tilapia ...

Durante o estabelecimento de confrontos entre indivíduos da mesma espécie, os fatores usualmente descritos como mediadores para o acesso a informações do oponente são sinais visuais, tais como tamanho, padrões de coloração e comportamentos ritualizados. Apesar da importância dos sinais visuais para comunicação em peixes, outros sinais são importantes neste complexo sistema. Considerando o meio aquático e a dispersão facilitada de substâncias químicas liberadas pelos indivíduos, espera-se que a sinalização química participe na avaliação de oponentes e na tomada de decisões antes e/ou durante um confronto. Assim, este estudo testou os efeitos de sinais químicos e sua integração com sinais visuais (tamanho do oponente) no comportamento agressivo em confrontos entre indivíduos da espécie Oreochromis nilocticus (Tilápia-do-Nilo). Para testar esta hipótese, duplas eram pareadas em uma condição em que os indivíduos podiam se ver, mas não havia contato mecânico ou químico entre eles. Durante os confrontos, o peixe focal da dupla era estimulado com sinais visuais e químicos de co-específicos, compondo as seguintes condições: estímulos químicos 1) água condicionada por um co-específico menor, 2) do mesmo tamanho 3) maior ou 4) água; e estímulos visuais 1) oponente do menor, 2) do mesmo tamanho ou 3) maior. Nos grupos que visualizaram um adversário menor, os diferentes tratamentos químicos não alteraram o comportamento agressivo do peixe focal. Ao visualizar um adversário do mesmo tamanho, os indivíduos que recebiam sinais químicos de co-específicos do mesmo tamanho e maiores apresentaram uma redução na expressão de ataques quando comparado ao grupo controle. Já ao visualizar um adversário maior, o tempo de exibição reduziu independentemente do estímulo químico e o número de ataques aumentou no grupo que recebia sinais químicos de co-específicos ...
Keywords: Peixe; Peixe - Comportamento; Peixe - Comportamento agressivo; Tilapia (Peixe); Tilápia-do-Nilo; Fishes